2005
DOI: 10.1177/104990910502200309
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of improved knowledge and skills after an elective rotation in a hospice and palliative care program for internal medicine residents

Abstract: There is compelling evidence that residents training in primary care need education in palliative care. Evidence for effective curricula is needed. The objective of this study was to test whether a clinical elective improves measures of knowledge and skill. Residents from three categorical training programs in internal medicine were recruited to an elective including clinical experiences in an acute hospital palliative care consultation service, on an acute hospice and palliative care unit, and in-home hospice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 34 publications
3
27
0
1
Order By: Relevance
“…Resident knowledge scores were approximately 60% overall on the pretest, which is comparable to previous studies in the literature. 10,13,21 The improvement in overall knowledge scores in the intervention group was statistically significant and consistent with the effect size seen in other studies. 10,18 Among individual test items, resident scores improved most notably in the dosage-based questions (i.e., dose frequency and dose equivalence).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Resident knowledge scores were approximately 60% overall on the pretest, which is comparable to previous studies in the literature. 10,13,21 The improvement in overall knowledge scores in the intervention group was statistically significant and consistent with the effect size seen in other studies. 10,18 Among individual test items, resident scores improved most notably in the dosage-based questions (i.e., dose frequency and dose equivalence).…”
Section: Discussionsupporting
confidence: 87%
“…Unlike previous studies that featured a lengthy, comprehensive education intervention or a dedicated palliative care rotation, 4,[9][10][11][12]18 our study evaluated a cheap, portable, and easily implemented educational tool. It could be used alone or added to an existing curriculum and may be easily updated with new information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have shown that completing a palliative care rotation improves trainee comfort and skill in symptom management. 15,16 Others have shown that a one-to two-day workshop can improve knowledge and comfort with providing palliative care. 17 Some have demonstrated the effectiveness of integrating longitudinal palliative care curricula or distance learning into postgraduate medical education for improving comfort and knowledge among trainees.…”
Section: Methods and Scopementioning
confidence: 99%
“…8 -10 Efforts to improve the quality of end-of-life care have been diverse, including increased educational programs, [11][12][13] development of palliative care units in hospitals, 14,15 and greater exposure to palliative care for physicians during residency training. 16 Despite these efforts, studies assessing the attitudes and knowledge of physicians about hospice and palliative care continue to show deficits in knowledge about managing pain 17,18 as well as hospice policies and services.…”
mentioning
confidence: 99%